The new David Espinoza - Aceves, Fred (2020)
Obsessed with the idea that he is not muscular enough and tired of being bullied, David, age seventeen, begins using steroids, endangering his relationships with family and friends
Ages 14 up.
Grades 10-12.
Keywords: Body image -- Fiction; Bodybuilding -- Fiction; Steroids -- Fiction; Drug abuse -- Fiction; Muscle dysmorphia -- Fiction; Bullying -- Fiction; Latin Americans -- Fiction; Young adult fiction